On the biological basis for psychodynamic collective principles - Alessandro Sergi (Mediterranean Journal of Clinical Psychology)
Clinical psychology represents a complex science deriving from different forms of knowledge (Benjamin, 2023; Davey, 2021; Lo Coco et al., 2022). Its multidisciplinary roots and current directions are considered as a form of strength (Lilienfeld Basterfield, 2020; Merlo Myles, 2024; Myles, 2022; Ricciardi et al., 2023; Warner et al., 2016; Wertheimer Puente, 2020).